Anti-Helicobacter pylori and antiulcerogenic activity of Aframomum pruinosum seeds on indomethacin-induced gastric ulcer in rats - Laure Brigitte Kouitcheu Mabeku; Blandine Nanfack Nana; Bertrand Eyoum Bille; Roland Tchuenteu Tchuenguem; Eveline Nguepi (Taylor & Francis Group, 2017)
Context: Peptic ulcer is one of the most common diseases affecting mankind. Although there are many products used for its treatment, most of these products produce severe adverse reactions requiring the search for novel compounds. Some Afromomum species are used traditionally to cure acute gastritis. Objective: To evaluate the antiulcer activity of the methanol extract of Aframomum pruinosum Gagnepain (Zingiberaceae) seeds against two major etiologic agents of peptic ulcer disease; Helicobacter pylori and non-steroidal anti-inflammatory drugs. Materials and methods: The anti-Helicobacter activity of A. pruinosum was evaluated using the broth microdilution method. After oral administration of indomethacin (5 mg/kg) for 5 consecutive days, gastric ulcerated animals were divided into control group and five other groups: three groups that recieved respectively 125, 250 and 500 mg/kg of plant extract, the fourth group received Maalox (50 mg/kg) and the fifth group, Misoprostol (100 μg/kg), respectively, for 5 days. Ulcer areas, gastric mucus content and nitric oxide gastric levels of animals were assessed 24 h after this treatment. Results: A. pruinosum extract shows a moderate anti-Helicobacter activity with an MIC value of 128 μg/mL. A. pruinosum extract, like Misoprostol and Maalox, markedly reduces the % of ulcerated area from 8.15 ± 0.33 to 1.71 ± 0.44% (500 mg/kg). It also increased significantly mucus and NO gastric production with respective values of 4.44 ± 1.35 and 965.81 ± 106.74 μmol/g (500 mg/kg). Discussion and conclusion: These findings suggest that A. pruinosum methanol extract possesses antiulcer properties as ascertained by the comparative decreases in ulcer areas, increase of mucus and NO gastric production.